Genetic Characteristics of Human Parainfluenza Virus Types 1–4 From Patients With Clinical Respiratory Tract Infection in China - Shao, Nan; Liu, Bo; Xiao, Yan; Wang, Xinming; Ren, Lili; Dong, Jie; Sun, Lilian; Zhu, Yafang; Zhang, Ting; Yang, Fan (Frontiers in Microbiology, 2021)
The human parainfluenza viruses (HPIV1–4) impact human health worldwide through acute respiratory tract infections. However, there are no current effective antivirals or licensed vaccines that can prevent infection, and sequence information for Human parainfluenza viruses (HPIVs), epidemic in China, is inadequate. Therefore, to shed further light on viral genetic diversity and evolution, we collected samples from patients infected with HPIV1–4 in China from 2012 to 2018 and sequenced the genetic information of the viruses. We obtained 24 consensus sequences, comprised 1 HPIV1, 2 HPIV2, 19 HPIV3, and 2 HPIV4A. Phylogenetic analyses classified 1 HPIV1 into clade 2, and 2 HPIV4 sequences into cluster 4A. Based on haemagglutinin-neuraminidase (HN) gene, a new sub-cluster was identified in HPIV2, named G1c, and HPIV3 sequences were divided into the genetic lineage of C3a and predominantly C3f. The results indicated that the lineages among sub-cluster C3, and HPIV1 to 4, had co-circulated in China. A recombination analysis indicated that a putative recombination event may have occurred at the HN gene of HPIV3. Furthermore, an amino acid substitution (R73K) in the fusion (F) protein, likely resistant to neutralization by site B monoclonal antibodies (MAbs), naturally occurred in a HPIV3 (PUMCH14028/2014) within C3a. An amino acid substitution (A281V), related to a variant selected with a monoclonal antibody, was found in the HN protein region of another HPIV3 (PUMCH13961/2014) that belonged to C3f. These results might provide support for virus evolution, vaccine development, and HPIV-related respiratory disease monitoring.